Fly Ash Zeolite as Permeable Reactive Barrier for Prevention of Groundwater Contamination Due to Coal Ash Disposal - Prasad, Bably; Sangeeta, Kumari; Tewary, B.K. (Asian Journal of Chemistry, 2011)
Prevention of groundwater contamination by using permeable reactive barrier (PRB) or zeosynthetic liner is a new and innovative technology. Permeable reactive barrier's are constructed underground across the flow path of contaminated ground water. The contaminants are removed from contaminated water by geochemical process taking place in the reactive material of the permeable reactive barrier. The suitable materials used in permeable reactive barrier’s are commonly activated carbon, zeolites, clay minerals and others. Fly ash produced due to burning of coal in thermal power plants can be converted into zeolitic mineral and the prepared zeolite can be used as permeable reactive barrier (zeosynthetic liner) to react with contaminants of leachate water of coal ash and make it clean. The process would reduce contamination of groundwater of coal ash filled pond or abandoned opencast mine, if the ash pond or open cast mine is filled with coal ash and lining of fly ash zeolite at its bottom. In the present work, laboratory scale study has been carried out to convert fly ash into fly ash zeolite and the prepared fly ash zeolite has been used as permeable reactive barrier and found that it can be successfully utilize as effective permeable reactive barrier (zeosynthetic liner) for prevention of groundwater contamination.